Differential response of corals to regional mass-warming events as evident from skeletal Sr/Ca and Mg/Ca ratios - Clarke, H.; D'Olivo, J.; Falter, J.; Zinke, Jens; Lowe, R.; McCulloch, M. (Wiley-Blackwell Publishing, 2017)
During the summer of 2010/2011, a regional marine heat wave resulted in coral bleaching of variable severity along much of the western coastline of Australia. At Ningaloo Reef, a 300 km long fringing reef system and World Heritage site, highly contrasting coral bleaching was observed between two morphologically distinct nearshore reef communities located on either side of the Ningaloo Peninsula: Tantabiddi (~20% bleaching) and Bundegi (~90% bleaching). For this study, we collected coral cores (Porites sp.) from Tantabiddi and Bundegi reef sites to assess the response of the Sr/Ca temperature proxy and Mg/Ca ratios to the variable levels of thermal stress imposed at these two sites during the 2010/2011 warming event. We found that there was an anomalous increase in Sr/Ca and decrease in Mg/Ca ratios in the Bundegi record that was coincident with the timing of severe coral bleaching at the site, while no significant changes were observed in the Tantabiddi record. We show that the change in the relationship of Sr/Ca and Mg/Ca ratios with temperature at Bundegi during the 2010/2011 event reflects changes in related coral "vital" processes during periods of environmental stress. These changes were found to be consistent with a reduction in active transport of Ca2+ to the site of calcification leading to a reduction in calcification rates and reduced Rayleigh fractionation of incorporated trace elements.